2011
DOI: 10.1002/bem.20681
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and physiological responses in humans exposed to a TETRA base station signal in relation to perceived electromagnetic hypersensitivity

Abstract: Terrestrial Trunked Radio (TETRA) technology ("Airwave") has led to public concern because of its potential interference with electrical activity in the brain. The present study is the first to examine whether acute exposure to a TETRA base station signal has an impact on cognitive functioning and physiological responses. Participants were exposed to a 420 MHz TETRA signal at a power flux density of 10 mW/m(2) as well as sham (no signal) under double-blind conditions. Fifty-one people who reported a perceived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 31 publications
1
10
0
6
Order By: Relevance
“…While all three participants displayed an increased symptom severity and were confident that they could detect the presence of RF‐EMF in the RF ON exposure condition compared to RF OFF in the initial open‐label trial, no significant differences in symptom severity or exposure detection between the RF ON and sham conditions were found in the double‐blind trials. These findings correspond to those reported by Eltiti et al [] and Wallace et al [], who found that IEI‐EMF participants had a greater symptomatic response in an initial open‐label active trial compared to sham, but no difference in subsequent double‐blind trials. Likewise, in a study similar to the present investigation, van Moorselaar et al [] reported that IEI‐EMF participants were unable to correctly identify when they were being exposed during double‐blind testing, despite participants reacting to the exposure in an initial unblinded test.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…While all three participants displayed an increased symptom severity and were confident that they could detect the presence of RF‐EMF in the RF ON exposure condition compared to RF OFF in the initial open‐label trial, no significant differences in symptom severity or exposure detection between the RF ON and sham conditions were found in the double‐blind trials. These findings correspond to those reported by Eltiti et al [] and Wallace et al [], who found that IEI‐EMF participants had a greater symptomatic response in an initial open‐label active trial compared to sham, but no difference in subsequent double‐blind trials. Likewise, in a study similar to the present investigation, van Moorselaar et al [] reported that IEI‐EMF participants were unable to correctly identify when they were being exposed during double‐blind testing, despite participants reacting to the exposure in an initial unblinded test.…”
Section: Discussionsupporting
confidence: 91%
“…Indeed, sham exposures alone have been found to be sufficient to trigger symptoms in IEI‐EMF participants [Wilén et al, ; Oftedal et al, ; Nam et al, ]. Two studies have also reported an increase in symptoms in an initial non‐blinded active exposure condition, compared to sham, but have then found no significant differences between active and sham conditions in subsequent double‐blind trials [Eltiti et al, ; Wallace et al, ]. Similarly, a recent study reported that IEI‐EMF participants were unable to correctly identify when they were being exposed under double‐blind conditions, despite an initial verification that they could detect active from sham conditions in an open‐label trial [van Moorselaar et al, ].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, adolescents with inattention are at a higher risk of other psychiatric illnesses such as mood and conduct disorders, and substance abuse [ 18 , 19 ]. However, in a study using a MP exposure device, no difference in attention was observed between the sham and MP exposure groups [ 20 , 21 ]. Attention functions may also be differentially enhanced after exposure to the electromagnetic field emitted by MP [ 22 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…105-119) and cognitive function (e.g. [120][121][122][123][124][125][126][127][128][129][130][131]. A few investigations were about effects on glucose metabolism (132, 133) and regional cerebral blood flow (134,135), applying PET scan imaging.…”
Section: Neurological Effects Of Radio-frequency Radiationmentioning
confidence: 99%